2002
DOI: 10.1074/jbc.m203325200
|View full text |Cite
|
Sign up to set email alerts
|

The Gene e.1 (nudE.1) of T4 Bacteriophage Designates a New Member of the Nudix Hydrolase Superfamily Active on Flavin Adenine Dinucleotide, Adenosine 5′-Triphospho-5′-adenosine, and ADP-ribose

Abstract: The T4 bacteriophage gene e.1 was cloned into an expression vector and expressed in Escherichia coli, and the purified protein was identified as a Nudix hydrolase active on FAD, adenosine 5-triphospho-5-adenosine (Ap 3 A), and ADP-ribose. Typical of members of the Nudix hydrolases, the enzyme has an alkaline pH optimum (pH 8) and requires a divalent cation for activity that can be satisfied by Mg 2؉ or Mn 2؉ . For all substrates, AMP is one of the products, and unlike most of the other enzymes active on Ap 3 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…Here, we showed that chloroplastic AtNUDX23 had FAD pyrophosphohydrolase activity, by which FAD was hydrolyzed to FMN and AMP (Tables I and II). Nudix hydrolases having FAD pyrophosphohydrolase activity have been identified in bacteria and bacteriophage (Xu et al, 2002;Tirrell et al, 2006). Recently, the characteristics of a bifunctional enzyme (AtFMN/FHy) with activities of riboflavin kinase and FAD synthetase in Arabidopsis were reported (Sandval and Roje, 2005).…”
Section: Fad Pyrophosphohydrolasementioning
confidence: 99%
See 1 more Smart Citation
“…Here, we showed that chloroplastic AtNUDX23 had FAD pyrophosphohydrolase activity, by which FAD was hydrolyzed to FMN and AMP (Tables I and II). Nudix hydrolases having FAD pyrophosphohydrolase activity have been identified in bacteria and bacteriophage (Xu et al, 2002;Tirrell et al, 2006). Recently, the characteristics of a bifunctional enzyme (AtFMN/FHy) with activities of riboflavin kinase and FAD synthetase in Arabidopsis were reported (Sandval and Roje, 2005).…”
Section: Fad Pyrophosphohydrolasementioning
confidence: 99%
“…Reaction product(s) FMN and/or AMP were detected (data not shown). The K m value for FAD (9.1 6 0.9 mM) was markedly lower than that of Paenibacillus thiaminolyticus YZGD (Tirrel et al, 2006) and T4 bacteriophage nudE.1 (Xu et al, 2002;Table II). On the other hand, the enzyme showed low affinity (386 6 76 mM) for ADP-Rib.…”
mentioning
confidence: 99%
“…T4 biology will "bootstrap" us to the recognition of similar biochemical processes in related phage while identifying genes and proteins that are novel to VOL. 67, 2003 BACTERIOPHAGE T4 GENOME 131 (1204), and ORF 24.1 (rnlB) encodes a second T4 RNA ligase related to the RNA-editing enzymes of trypanosomes and those present in sequenced Archaea (426). T4 will be a handy genetic and biochemical tool for detailed studies of their respective enzymatic activities.…”
Section: A Glimpse At Genome Diversity and Evolution In T4-type Phagesmentioning
confidence: 99%
“…The nucleoside diphosphate linked to some other moiety X (Nudix) protein family, formerly called the MutT protein family, consists of about 800 proteins in more than 200 species from all kingdoms (1). This group of proteins may be divided into subfamilies based on the substrate specificity: ADP-ribose, dinucleoside polyphosphates, NADH, nucleotide sugars, or ribo-and deoxyribonucleoside triphosphates (2).…”
mentioning
confidence: 99%